Chemical and biological weapons and terrorism - Tu, Anthony T. (CRC Press, 2018)
Chemical agent and weapons -- Biological agent and weapon -- Example of chemical war in Iran-Iraq War -- Example of chemical terrorism: sarin terrorism in Japan -- Example of bio-terrorism: anthrax terrorism in the U.S -- Detection and identification of chemical and biological weapons -- Protection from chemical and biological agents -- Decontamination of chemical and biological weapons and terrorism -- Destruction of chemical weapon -- How to deal with terrorism